The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1902/jop.1995.66.7.552
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor Effects on the Expression of Collagenase and TIMP‐1 in Periodontal Ligament Cells

Abstract: The fibroblast is a prominent cellular component of the periodontal ligament. It is believed to play an important role in collagen metabolism in health and disease. The turnover of collagen in the periodontal ligament is believed to be controlled by the balance between collagen synthesis and degradation. The family of matrix metalloproteinases and their inhibitors is one of the mechanisms which regulates this balance. The factors that regulate the synthesis of collagenase and its inhibitor, TIMP-1, by the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 26 publications
4
34
1
Order By: Relevance
“…IL-1β is a potent pro-inflammatory cytokine produced mainly by macrophages in injured tissues and upregulates the expression of other inflammatory mediators, including COX-2, IL-6, MMP-1, and MMP-3. In fibroblasts, for example, IL-1β induces the expression of MMPs (Tewari et al, 1994;Alvares et al, 1995), which could initiate the degradation and remodeling of tissues (e.g., tendons) in response to mechanical loading (Vailas et al, 1985). COX-2 is a major marker of tissue inflammation (Gilroy et al, 1998;Lipsky, 1999) that converts arachidonic acid into prostaglandins, such as PGE 2 .…”
Section: Introductionmentioning
confidence: 99%
“…IL-1β is a potent pro-inflammatory cytokine produced mainly by macrophages in injured tissues and upregulates the expression of other inflammatory mediators, including COX-2, IL-6, MMP-1, and MMP-3. In fibroblasts, for example, IL-1β induces the expression of MMPs (Tewari et al, 1994;Alvares et al, 1995), which could initiate the degradation and remodeling of tissues (e.g., tendons) in response to mechanical loading (Vailas et al, 1985). COX-2 is a major marker of tissue inflammation (Gilroy et al, 1998;Lipsky, 1999) that converts arachidonic acid into prostaglandins, such as PGE 2 .…”
Section: Introductionmentioning
confidence: 99%
“…These tendon conditions are accompanied by inflammation through up-regulation of proinflammatory cytokines, COX-2, matrix metalloproteinase (MMP) 2 expression, and prostaglandin E 2 (PGE 2 ) production. This could initiate the degradation and remodeling of tendons in response to mechanical loading (1,2).…”
mentioning
confidence: 99%
“…The turnover of collagen in the periodontal ligament is controlled by the balance between collagen synthesis and degradation. The family of matrix metalloproteinases and their inhibitors is one of the mechanisms which regulate this balance 36) . In this study, we quantified the MMP-1 mRNAs extracted from PDL fibroblasts after LPS stimulation, and normalized with GAPDH mRNA levels 37) .…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…Alvares et al reported that IL-1βexerted profound effect in MMP-1 synthesis in PDL fibroblasts, but no effects in TIMP-1 at the mRNA level. They suggested that cytokines differentially and specifically regulate expression of collagenase mRNA in human PDL 36) . LPS is known to exert profound effect on the protein expression by host cells.…”
Section: ⅳ Discussionmentioning
confidence: 99%